PARTISIPASI DAN KONTRIBUSI EKONOMI IBU-IBU RUMAH TANGGA PETANI DALAM PENGELOLAAN RUMPUT LAUT DI KELURAHAN BINTARORE KECAMATAN UJUNG BULU KABUPATEN BULUKUMBA - Asriyanti Syarif (OCTOPUS : JURNAL ILMU PERIKANAN, 2016)
The aim of this study to determine the economics participation and contribution of women farmers households in the Bintarore village Ujung Bulu sub-district Bulukumba regency.  The population in this study are 132 people, drawn sample by 20% from a total population so that 26 housewives farmers were obtained. Sampling is done by simple random sampling method. Data analysis that used in this research is qualitative analysis through interpretation and comprehension. Furthermore, the percentage of housewives farmers participation in the pre-production and post-harvest stage of seaweed farming in Bintarore village, Ujung Bulu sub-district, Bulukumba regency, calculates the income of housewives in seaweed production is number of expenses made by housewives Ladder in pre-production activities multiplied by price (Rp / stretch).The results showed that housewives farmers household participated more in pre-production activities compared with post-production activities, the economic impact for housewives provided additional income for the family despite the small nominal value.